Blockchain-Enabled CSR Transparency: A Systematic Review. - Ojog, Silviu; Miron, Alina-Andrea (Pertanika Journal of Social Sciences & Humanities)
Corporate Social Responsibility (CSR) reporting has become an important mechanism for organisations to communicate their environmental, social, and governance commitments to stakeholders. Although recent regulatory initiatives have sought to improve the consistency and reliability of CSR disclosures, concerns regarding transparency, data integrity, and reporting of credibility remain. In response to these challenges, blockchain technology has gained attention as a potential tool for strengthening CSR reporting practices. This study explores the role of blockchain in CSR reporting through a systematic review of 21 publications covering blockchain technology, smart contracts, and non-fungible tokens (NFTs). Drawing evidence from academic, technical, and industry sources, the review examines how these technologies can support greater transparency, accountability, and stakeholder trust while highlighting current implementation challenges and research gaps. The findings suggest that CSR reports can be recorded and verified as NFTs on a blockchain network, offering a secure and traceable approach to reporting. Unlike conventional NFTs used for digital assets, CSR-related NFTs possess distinctive characteristics, including non-transferability and the need for regulatory oversight during their creation and validation. This study contributes to the emerging literature by proposing a blockchain-based CSR reporting architecture that integrates smart contracts and NFT standards while recognising the roles of companies, verifiers, and regulatory authorities. The proposed framework also advances understanding of the practical and conceptual considerations associated with CSR-focused NFTs, providing a foundation for future research and implementation.